Duodenal ulcer healing and Helicobacter pylori eradication with 10 day omeprazole amoxicillin and clarithromycin therapy - Mehmet CİNDORUK and Ahmet GÖRDÜLÜ and Şükrü DUMLU and Zeynep AKI and Selahattin ÜNAL (Turkish Journal of Gastroenterology, 2019)
-